2019
DOI: 10.7554/elife.49180
|View full text |Cite
|
Sign up to set email alerts
|

A mechanism in agrin signaling revealed by a prevalent Rapsyn mutation in congenital myasthenic syndrome

Abstract: Neuromuscular junction is a synapse between motoneurons and skeletal muscles, where acetylcholine receptors (AChRs) are concentrated to control muscle contraction. Studies of this synapse have contributed to our understanding of synapse assembly and pathological mechanisms of neuromuscular disorders. Nevertheless, underlying mechanisms of NMJ formation was not well understood. To this end, we took a novel approach – studying mutant genes implicated in congenital myasthenic syndrome (CMS). We showed that knock-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 82 publications
(158 reference statements)
3
34
0
Order By: Relevance
“…50 Recent studies also revealed that the scaffold protein Rapsyn has a RING domain with E3 ligase activity, and it catalyzes the neddylation of AChRs which is critical for AChRs clustering. 68,69 Although the APC/C E3 ligase is known as an anaphase-promoting complex that regulates cell cycle transition, 27,29 it is also expressed and plays a role in postmitotic cells. 30,33,34,58,70 Although APC2 is reported to regulate invertebrate neuromuscular synapse size, 30 vertebrate NMJs are cholinergic and regulated by different molecular pathways.…”
Section: Discussionmentioning
confidence: 99%
“…50 Recent studies also revealed that the scaffold protein Rapsyn has a RING domain with E3 ligase activity, and it catalyzes the neddylation of AChRs which is critical for AChRs clustering. 68,69 Although the APC/C E3 ligase is known as an anaphase-promoting complex that regulates cell cycle transition, 27,29 it is also expressed and plays a role in postmitotic cells. 30,33,34,58,70 Although APC2 is reported to regulate invertebrate neuromuscular synapse size, 30 vertebrate NMJs are cholinergic and regulated by different molecular pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Following MuSK-DOK7 activation, several other adaptor proteins are phosphorylated and recruited, in particular Crk and Crk-L (Hallock et al, 2010 ), as well as other kinases, such as Abl (Finn et al, 2003 ), Scr (Mittaud et al, 2001 ), and the GTPases Rac1 and Rho which induce cytoskeleton modifications contributing to the maturation of AChR clusters (Weston et al, 2003 ; Bai et al, 2018 ). The whole cascade converges into the phosphorylation of the AChR subunits and rapsyn; rapsyn is a structural protein that self-aggregates providing a scaffold that anchors AChRs with the actin cytoskeleton—through the mediation of microtubule actin cross-linking factor 1 (MACF1)—to form the mature clusters (Borges and Ferns, 2001 ; Lee et al, 2009 ; Zuber and Unwin, 2013 ; Oury et al, 2019 ; Xing et al, 2019 ; Figure 1C ).…”
Section: Pathophysiology Of Musk-mgmentioning
confidence: 99%
“…While it is clear that Rapsyn is activated after MuSK dimerization, the underlying mechanisms remain poorly understood. A very recent report indicates that agrin:LRP4-mediated MuSK activation induces tyrosine phosphorylation of Rapsyn, which is required for its self-association and E3 ligase activity (Xing et al, 2019). This reveals an intriguing scenario where the initial trigger of the signaling cascade (MuSK) directly induces a multitude of cellular events, including the ultimate activation of the protein that clusters AChRs on the post-synaptic membrane.…”
Section: "Canonical" Nmj Signaling Requires Musk Activationmentioning
confidence: 99%